The Effect Of Fishbowl Strategy Toward Student’s Speaking: Investigasi Film Kartun Terhadap Keterampilan Menyimak Siswa - Muawanah, Muawanah (LPPM Institut Studi Islam Sunan Doe, 2023)
The aims of this study to find out the effect of fishbowl strategy toward students’s speaking skill ability at the second year students of MA Mu’allimat NW Pancor. Designed as experimental research which the researcher divide the sample into experimental group and control group. Both of the group were given the same test. The test consisted post-test. The population was all the second year students of MA Mu’allimat NW Pancor that consisted of six classes which were 248 students. The sample was 36 students that were taken by random sampling technique. The data was analyzed by using descriptive statistic. The result of the data analysis shown that the lowest score of the students who were in the experimental group was 53 and the highest score was 80. While, those who in the control group was 52 for the lowest score and 76 for the highest score. The result of this research, it was found out that the effect of fishbowl strategy between the experimental and control group were significance. The control group got 1101, while the experimental group got 1227. In conclusion, the fishbowl strategy had significant effect in teaching speaking.